2020
DOI: 10.1002/adma.202006647
|View full text |Cite
|
Sign up to set email alerts
|

Sensing of COVID‐19 Antibodies in Seconds via Aerosol Jet Nanoprinted Reduced‐Graphene‐Oxide‐Coated 3D Electrodes

Abstract: Rapid diagnosis is critical for the treatment and prevention of diseases. An advanced nanomaterial‐based biosensing platform that detects COVID‐19 antibodies within seconds is reported. The biosensing platform is created by 3D nanoprinting of three‐dimensional electrodes, coating the electrodes by nanoflakes of reduced‐graphene‐oxide (rGO), and immobilizing specific viral antigens on the rGO nanoflakes. The electrode is then integrated with a microfluidic device and used in a standard electrochemical cell. Whe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
240
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(259 citation statements)
references
References 46 publications
(47 reference statements)
1
240
0
2
Order By: Relevance
“…Ali et al created a three-dimensional reduced-graphene-oxide electrode and integrated with a microfluidic device as an electrochemical sensor. 200 Such 3D electrodes were functionalized with viral antigens to enable sensitive detection of antibodies specific to SARS-CoV-2, with the detection limit down to 2.8 × 10 −15 M. Fabiani et al applied the magnetic beads with the carbon black-based electrode to realize a miniaturized electrochemical sensor for SARS-CoV-2 detection (Fig. 15a).…”
Section: Electrochemical Biosensorsmentioning
confidence: 99%
“…Ali et al created a three-dimensional reduced-graphene-oxide electrode and integrated with a microfluidic device as an electrochemical sensor. 200 Such 3D electrodes were functionalized with viral antigens to enable sensitive detection of antibodies specific to SARS-CoV-2, with the detection limit down to 2.8 × 10 −15 M. Fabiani et al applied the magnetic beads with the carbon black-based electrode to realize a miniaturized electrochemical sensor for SARS-CoV-2 detection (Fig. 15a).…”
Section: Electrochemical Biosensorsmentioning
confidence: 99%
“…Moreover, a nanomaterial-based biosensor that could rapidly detect COVID-19 antibodies was developed [ 104 ]. The biosensing platform was made using 3D bioprinted electrodes coupled with nanoflakes of reduced-graphene-oxide (rGO).…”
Section: Diagnosticsmentioning
confidence: 99%
“…The same strain of virus was also killed using a carbon nanotube-coated glass fiber prepared via an electro-aerodynamic deposition technique under ambient conditions (Park and Hwang 2014 ). Recently, specific viral antigens immobilized on reduced GO biosensors via the aerosol jet nano-printing technique were used to detect COVID‐19 antibodies within seconds (Ali et al 2020 ). It was also shown that Cu can inhibit the replication of SARS-CoV-2, MERS, or influenza and Cu oxide can be used in face masks, protective clothing, and filters to prevent bacterial and viral transmission (Cortes and Zuñiga 2020 ).…”
Section: Biomedical Applicationsmentioning
confidence: 99%